Integrating Contextual Approach and Islamic Values in Three-Variable Linear Equations System Module - Riyana Ulfaini; Dian Permatasari (Jurnal Tadris Matematika, 2022)
In the 2013 Curriculum, students are expected to have knowledge and skills in lessons and also have spiritual and social attitudes. Therefore, it is necessary to connect learning material with real-life and religious aspects. This research aims to develop a mathematical module based on a contextual approach that integrates Islamic values ​​into a valid Three-variable Linear Equations System. This research is a research and development (R&D). This research was designed by following Richey and Klein's development steps, namely the PPE model. The PPE model consists of 3 steps: planning, production, and evaluation. The data collection instruments used in this study were a material expert validity assessment sheet and a media expert validity assessment sheet. The data that has been obtained were analyzed using average and percentage calculations and classifying the results based on predetermined criteria. The results showed that the mathematics module based on a contextual approach that integrated Islamic values ​​in the material of a Three-variable Linear Equations System met the valid criteria based on the assessment of expert validators. This shows that the module have "good" qualification with an average score of 83.40% by the material expert validator and "good" qualification with an average score of 87.5% by the media expert validator.